Implemention of Islamic Religious Education Curriculum Based on Integrated Islamic School Quality Standards at SMAIT Nurul Ilmi Tenggarong - Meyfa Rizkia Al Aswa; Salsa Nazwa Maharani; Muhammad Ilham Ainurrojab; Khaerul Azmi; Riziq Aulia Rahman; Maryam Maryam; Qurrotul Aini Mufidah (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The implementation of the Islamic Religious Education (IRE) curriculum based on the Quality Standards of Integrated Islamic Schools (IIS) is a strategic effort to integrate spiritual values with national academic standards. This study aims to analyze the planning, implementation, evaluation, as well as the supporting and inhibiting factors in the implementation of the PAI curriculum at SMAIT Nurul Ilmi Tenggarong. this research employed a qualitative method with a descriptive design. Data were collected through observation and in-depth interviews to gain a detailed understanding of the processes of planning, implementation, and evaluation of the curriculum, the results indicate that the curriculum implementation has been carried out systematically through the preparation of learning instruments aligned with the Merdeka Curriculum and integrated with Islamic values. The learning implementation includes intracurricular activities and religious habituation programs such as congregational prayers and Qur’an recitation. Evaluation is conducted comprehensively, covering cognitive, affective, and psychomotor aspects, with a focus on strengthening students’ Islamic character. Although there are challenges related to administrative aspects and the diverse backgrounds of students, this implementation has proven to contribute positively to the overall improvement of educational quality in a holistic manner.